Effect of Drought Stress on Morphology and Chlorophyll Content of Sorghum (Sorghum bicolor L. Moench) - Rahardhianto, Arsetyo; Raharjo, Sulistyo Yusuf; Nugroho, Sandi Luqman; Purwinto, Rahmanaji Setyo; Soleh, Mohamad Badrus; Sugiharto, Bambang (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2025)
Sorghum is a type of cereal plant that easily adapts to stressful environmental conditions. Sorghum has many benefits as it can be used as food, feed, and energy sources, making it a promising crop for development on dry land in Indonesia. Drought impacts plants during their growth process, causing physiological and biological changes. This study aims to determine the effect of drought stress on the morphology and chlorophyll content of sorghum plants. Preliminary research was conducted by planting three varieties of sorghum (Numbu, Super 1, and Super 2). Subsequent planting involved selecting the variety most resistant to drought based on data analysis of several parameters. The basic design used in this experiment was a completely randomized design (CRD) with one factor: the level of drought stress, which had four levels -no drought stress as a day 0 (control) and drought stress for 3, 6 and 9 days by withholding water. The results showed a decrease in the total chlorophyll content of the leaves over time. Drought stress for 6 and 9 days without watering resulted in water content dropping below 25%, indicating severe drought stress and disrupting plant growth. Severe drought stress was characterized by low soil and leaf water content, yellowing and curling of the leaves.